Investigation Of Dissolution Performance And Physical Characterization On Development Of Solid Dispersion Dosage Form - Farhan, Ahmed Bassam (2020)
Solid dispersion (SD) formulation has attracted much attention due to its potential in enhancing dissolution performance of poorly soluble active pharmaceutical ingredients (API). However, an overview of the dissolution performance of SDs implies inconsistent degree of dissolution improvement of poorly soluble APIs in SD. Therefore, the main objective of this study is to determine the criteria of a good carrier system and drug candidate for enhanced dissolution performance of a solid dispersion system for a poorly soluble drug and dosage form consideration particularly the impact of compaction. To achieve these objectives, several SD systems were prepared in this study by spray drying and quenched